HIPEC-induced acute kidney injury: a retrospective clinical study and preclinical model - Liesenfeld, Lukas; Wagner, Benedikt; Hillebrecht, Christian; Brune, Maik; Eckert, Christoph; Klose, Johannes; Schmidt, Thomas; Büchler, Markus W.; Schneider, Martin (Annals of surgical oncology, 2022)
Hyperthermic intraperitoneal chemotherapy (HIPEC) combined with cytoreductive surgery (CRS) is the treatment of choice for selected patients with peritoneal malignancies. HIPEC is accompanied by moderate-to-high patient morbidity, including acute kidney injury. The significance of nephrotoxic agents such as cisplatin versus hyperthermia in HIPEC-induced nephrotoxicity has not been defined yet.
Online veröffentlicht: 14. Juli 2021
Gesehen am 17.07.2023